Application of The Jigsaw Type Cooperative Learning Model Reviewed From Critical Thinking In The Subject of Aqidah Akhlaq Material - Nasrulloh, Muhammad Farid; Inayaturrohmah, Inayaturrohmah; Satiti, Wisnu Siwi (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The application of the Jigsaw type cooperative learning model in terms of critical thinking skills in the Aqidah Akhlaq subject Material. This research aims to determine the effectiveness and process of implementing the Jigsaw Type Cooperative Learning Model in View of Critical Thinking Ability in the Subject of Aqidah Akhlaq Material: Exemplary Characteristics of Abu Bakar Ash Shiddiq Class VIII MTSN 4 Jombang. This application makes it easier for students to understand the material, increases students' experience, improves critical thinking skills, especially in the subject of Aqidah Akhlaq. Critical thinking as a cognitive skill includes activities of interpretation, analysis, evaluation, inference, ability to explain, self regulation. This research method uses the Pre-Experimental Design method with One-Group Pretest-Posttest Design. This research data was collected through tests, interviews and documentation. Data was analyzed using quantitative analysis techniques. The results of this research show that there is a comparison of the average student score after using the Jigsaw type cooperative learning model of 76 and before using the Jigsaw type cooperative learning model of 56.00, apart from that it is also proven by calculating the t value of -13,190 with df = 39. The Ttable obtained of the number (n) = 40 with degrees of freedom (df) = n-1 or 40-1 = 39. The results obtained for t table are 2.021, based on the value of this research tcount > t table (-13.190 > 2.021) then H0 is rejected and H1 is accepted. So it can be concluded that the application of the jigsaw type cooperative learning model can improve student learning outcomes and students' thinking abilities.